Implementation of Community Empowerment Communication in the Need of Environmental Food Security through the Program “Bandung Agri Market” - Sri Mulyani, Henny; Agustin, Herlina; Zulfan, Ipit (International Journal of Psychosocial Rehabilitation, 2019)
Bandung Agri Market (BAM) is a communication tool for urban farming activists in marketing the results of gardening groups in the city of Bandung. BAM was inaugurated and held for the first time by the Mayor of Bandung, Ridwan Kamil, in 2014. BAM is managed by the Bandung City Food and Agriculture Service and has been held regularly since 2014, with the aim of empowering urban farming activists to market their crops independently without being dependent on the traditional and modern markets. Community empowerment efforts are tailored to the potential, problems, and needs of the local community. This study aims to see how the Bandung Agri Market program can be a forum for community independence in supporting food and environmental security, measuring community empowerment, and learning the obstacles faced in implementing BAM. The study used a constructivist paradigm with a qualitative descriptive method; data was collected through interview techniques, field observations, and library studies. The research sources are Food and Agriculture Service Officers, BAM activity, and visitors. The results showed that BAM could be used as a forum for the independence of urban farming groups, communities, farmer groups, regional technical implementation units (UPTD) for nurseries, and small and medium enterprises (UKM). In the long run, the implementation of BAM contributes to increasing green open space. In its implementation, there are still communication barriers and technical obstacles.